2014
DOI: 10.3390/ijms15046741
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Bioactivity of N-Glycosyl-N'-(5-substituted phenyl-2-furoyl) Hydrazide Derivatives

Abstract: Condensation products of 5-substituted phenyl-2-furoyl hydrazide with different monosaccharides d-glucose, d-galactose,d-mannose, d-fucose and d-arabinose were prepared. The anomerization and cyclic-acyclic isomers were investigated by 1H NMR spectroscopy. The results showed that, except for the d-glucose derivatives, which were in the presence of β-anomeric forms, all derivatives were in an acyclic Schiff base form. Their antifungal and antitumor activities were studied. The bioassay results indicated that so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It has been reported that the compounds containing furan showed broad-spectrum bioactivities. A wide range of derivatives such as dibenzoylureas 15 , diacylhydrazines 16 17 18 19 20 21 , acylhydrazones 22 23 24 25 , semicarbazide 26 , pyrazole, 1,2,4-triazole 27 , 1,3,4-oxadiazole 28 , and carbamic acid esters 29 30 containing 5-phenyl-2-furan moiety has been synthesized and studied in our group for the development of novel chemical entities as a lead molecule in drug and agrochemical discovery. All the compounds showed diverse and significant bioactivities such as fungicidal, insecticidal, and antitumor activities.…”
mentioning
confidence: 99%
“…It has been reported that the compounds containing furan showed broad-spectrum bioactivities. A wide range of derivatives such as dibenzoylureas 15 , diacylhydrazines 16 17 18 19 20 21 , acylhydrazones 22 23 24 25 , semicarbazide 26 , pyrazole, 1,2,4-triazole 27 , 1,3,4-oxadiazole 28 , and carbamic acid esters 29 30 containing 5-phenyl-2-furan moiety has been synthesized and studied in our group for the development of novel chemical entities as a lead molecule in drug and agrochemical discovery. All the compounds showed diverse and significant bioactivities such as fungicidal, insecticidal, and antitumor activities.…”
mentioning
confidence: 99%
“…The outcome of coupling of acylhydrazines or thioacylhydrazines with various reducing saccharides has been reported to exist in solution as sugar hydrazones (acyclic forms) or glycosylhydrazides (cyclic forms) and often coexist in tautomeric equilibrium mixtures. ,,, The preference of adopting the open chain, cyclic structures, or an interconvertable equilibrated mixture of them has been synergistically effected by the basicity of hydrazines, reaction conditions, pH of the reaction mixture, solvent used in 1 H NMR spectra, as well as sugar configuration …”
Section: Resultsmentioning
confidence: 99%
“…Hydrazides have been described as useful key compound to synthesize various heterocyclic compounds . Hydrazides are reported to have different and rich biological properties . Hydrazones are used in electrophotography, due to their relatively simple synthesis, low molecular weight, and aperture‐conveying properties .…”
Section: Introductionmentioning
confidence: 99%